The Differences in Urokinase Plasminogen Activator System in Lung Cancer Patients Before and After Chemotherapy - Tri Wahju Astuti; Agustin Iskandar; Mufidatun Hasanah; Lindayanti Sumali; Dian Nugrahenny (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Lung cancer is still the leading cause of death for malignancies worldwide. Urokinase plasminogen activator (uPA), its soluble receptor (suPAR), and its inhibitor (PAI-1) play an important role in tumor invasion and metastasis. This study aimed to evaluate the differences in the urokinase plasminogen activator system (uPA, suPAR, and PAI-1) in lung cancer patients before and after chemotherapy.Methods: This research was an observational analytical study with a cross-sectional design. The subjects were 30, consisting of 17 lung cancer patients before chemotherapy and 13 lung cancer patients after chemotherapy for 4 or 6 cycles. The levels of serum uPA, suPAR, and PAI-1 were measured by enzyme-linked immunosorbent assay (ELISA). Results: In lung cancer patients before chemotherapy, there were no significant (p>0.05) differences in levels of serum uPA, suPAR, and PAI-1 between patients with stage III and IV. The highest serum uPA and suPAR levels were found in adenocarcinoma cell types and the highest serum PAI-1 level in adenoepidermoid cell types. After chemotherapy, serum suPAR and PAI-1 were significantly (p < 0.05) decreased in lung cancer patients. However, there were no significant (p>0.05) differences in the levels of serum uPA, suPAR, and PAI-1 between patients with chemotherapy responses for stable and progressive diseases. Conclusion: This study revealed that suPAR and PAI-1 levels were decreased in lung cancer patients who had received chemotherapy. This can occur due to decreased tumor cells activity.